Impact of Epidural Analgesia During Labor on Maternal and Child Neurodevelopmental Outcomes: A Quantitative Meta-Analysis - Shivanand, Shraavya; Ganiger, Fakirappa; Mugali, Jitendra; Gadad, Arun; Karthikaiselvan, GR; Hubli, Suhasini (Nepal Journal of Neuroscience, 2025)
Introduction: Childbirth poses significant physical and psychological challenges like increasing the risk of postpartum psychiatric disorders, including postpartum depression (PPD), anxiety and psychosis. Epidural analgesia (EA) is widely recognized for its efficacy in managing labor pain,its impact on maternal mental health and neonatal neurodevelopment remains uncertain. This meta-analysis evaluates the effects of EA on maternal psychiatric outcomes, including PPD, anxiety, mother-infant bonding, and autism spectrum disorder (ASD) in offspring. Methods: A systematic review of PubMed, Cochrane Library, and Scopus databases was conducted. Studies providing quantitative data on psychiatric outcomes, including odds ratios (ORs) were included. Data were analyzed using the DerSimonian and Laird random-effects model. Heterogeneity was assessed with Cochran’s Q and I² statistics, and publication bias was evaluated using funnel plots and Egger’s test. Sensitivity analyses ensured robustness. Results: This Meta-analysis included fifteen studies (n = 42,342 participants) which showed that using EA during labour reduced the risk of PPD (pooled OR: 0.56; I² = 42%) and Maternal Anxiety (pooled OR: 0.62; I² = 48%) and it also improved Mother-Infant Bonding (pooled OR: 1.45; I² = 38%). However, there was no significant association found between EA and ASD (pooled OR: 1.04; I² = 21%). Conclusion: Epidural analgesia offers notable benefits for maternal mental health, reducing PPD and anxiety while enhancing mother-infant bonding. These findings reinforce its value in labor management but highlight the need for further research on long-term effects and specific anesthetic agents.